2019
DOI: 10.1042/bcj20190095
|View full text |Cite
|
Sign up to set email alerts
|

The ChlD subunit links the motor and porphyrin binding subunits of magnesium chelatase

Abstract: Magnesium chelatase initiates chlorophyll biosynthesis, catalysing the MgATP2−-dependent insertion of a Mg2+ ion into protoporphyrin IX. The catalytic core of this large enzyme complex consists of three subunits: Bch/ChlI, Bch/ChlD and Bch/ChlH (in bacteriochlorophyll and chlorophyll producing species, respectively). The D and I subunits are members of the AAA+ (ATPases associated with various cellular activities) superfamily of enzymes, and they form a complex that binds to H, the site of metal ion insertion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…The ~140 kDa ChlH subunit binds the porphyrin substrate (182), and the ~40 kDa ChlI and ~80 kDa ChlD subunits belong to the ATPases Associated with various cellular Activities (AAA + ) superfamily. The current view is that ChlD is the physical and mechanistic link between the ChlI AAA+ motor and ChlH, which houses the site of metal ion chelation (183).…”
Section: The Transformation Of Protoix Into Chls -Chl Amentioning
confidence: 99%
“…The ~140 kDa ChlH subunit binds the porphyrin substrate (182), and the ~40 kDa ChlI and ~80 kDa ChlD subunits belong to the ATPases Associated with various cellular Activities (AAA + ) superfamily. The current view is that ChlD is the physical and mechanistic link between the ChlI AAA+ motor and ChlH, which houses the site of metal ion chelation (183).…”
Section: The Transformation Of Protoix Into Chls -Chl Amentioning
confidence: 99%
“…The BchD/ChlD subunit is composed of a C‐terminal integrin I domain preceded by a proline‐rich region and an N‐terminal domain similar to BchI/ChlI, but possesses no ATPase activity . Recently, it has been demonstrated that ChlD links the ATPase activity with the ChlH active site primarily through the integrin I domain . Assembly of the BchD/ChlD hexamer is generally assumed to be mediated by the N‐terminal BchI/ChlI‐homologous domain, while contribution from the integrin I domain is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The ChlI subunit from the cyanobacterium Synechocystis sp. PCC 6803 has been extensively characterized . The ChlI protomers can self‐assemble into a ring structure without ATP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations